‘Being,’ ‘Doing,’ and ‘Knowing’: An Autoethnography of Everyday Ethnicity - Esteban, Rolando C. (Philippine Social Sciences Review, 2021)
Globally, ethnicity – the “sense of fellow feeling” – is considered in terms of its disruptive effects in modern society. The paper departs from this ‘politicist’ position by probing, instead, into the everyday ethnicity – the self-defining comforts of routine and authenticity. It aims to understand my Ilongo-ness as second generation diasporant in polyethnic milieus in Mindanao and the role sugilanon in the natural language in fostering it. It tries to interweave experience with sugilanon in Hiligaynon, as narrative and storytelling. Fishman’s concept of everyday ethnicity as ‘being’, ‘doing’, and ‘knowing informs, frames, and hems the analysis. The genre that obtains from the analysis is not only realist but also descriptive, narrative, and interpretive. It hopes further to our understanding of the paradox of ethnicity that is always in flux even as it resists change.
Keywords: autoethnography, ethnicity, sugilanon, Hiligaynon